2022
DOI: 10.1002/tox.23468
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA OIP5‐AS1 promotes the stemness of lung cancer cells through enhancing Oct4 mRNA stability

Abstract: Long noncoding RNA (lncRNA) OIP5-AS1 was shown to facilitate drug resistance and metastasis in several tumors. As cancer stem cells (CSCs) have been elucidated as the origin of drug resistance and tumor progression, we speculate that lncRNA OIP5-AS1 holds critical roles in the CSC-like traits of lung cancer. Here, lncRNA OIP5-AS1 was found to be highly expressed in lung cancer cell spheres. Following experiments showed that OIP-AS1 knockdown reduced the CSC-like traits of lung cancer spheres, while overexpress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Increasing evidence has established that regulation of OCT4 expression plays a crucial role in the regulation of CSC properties in many human malignancies. Opa interacting protein 5-antisense RNA 1 (OIP5-AS1) promotes the stemness of lung cancer cells by enhancing OCT4 mRNA stability [ 40 ]. The results demonstrated that lncRNA OIP5-AS1 can confer lung cancer CSC-like traits by directly interacting with OCT4 mRNA, thus increasing OCT4 mRNA stability and expression, and knockdown of OCT4 could rescue the promoting effects of OIP5-AS1 overexpression on CSC-like traits.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence has established that regulation of OCT4 expression plays a crucial role in the regulation of CSC properties in many human malignancies. Opa interacting protein 5-antisense RNA 1 (OIP5-AS1) promotes the stemness of lung cancer cells by enhancing OCT4 mRNA stability [ 40 ]. The results demonstrated that lncRNA OIP5-AS1 can confer lung cancer CSC-like traits by directly interacting with OCT4 mRNA, thus increasing OCT4 mRNA stability and expression, and knockdown of OCT4 could rescue the promoting effects of OIP5-AS1 overexpression on CSC-like traits.…”
Section: Discussionmentioning
confidence: 99%
“…LncRNA opa‐interacting protein 5 antisense transcript 1 (OIP5‐AS1) also had a dysregulation in different cancers. Mechanically, it not only interacted with miRNAs to perform its function in ovarian cancer (OC), 66 endometrial carcinoma (EC), 67 and papillary thyroid cancer (PTC), 68 but could directly interact with Oct4 mRNA to promote its stability in lung cancer 69 . SEMA6A‐AS1 expression was decreased in HBV‐related HCC tissues compared with adjacent noncancerous tissues, and the expression level of SEMA6A‐AS1 was associated with prognosis of these patients 70 .…”
Section: Discussionmentioning
confidence: 99%
“…It is a key factor in gene regulation and also involved in the function of CSCs and EMT [ 105 ]. LncRNA OIP5-AS1 can directly interact with OCT4 mRNA, enhance the stability of OCT4 mRNA to increase OCT4 expression, and endow lung cancer cells with CSC characteristics [ 106 ]. The interaction between lncRNA and miRNA forms a competitive endogenous RNA (ceRNA) mode and possesses a negative feedback regulation mechanism.…”
Section: Introductionmentioning
confidence: 99%